Contribution of the Sulit Air Sepakat (SAS) Organization in Solok Regency - Zulfitri Yeni; Irwandi Irwandi; Syafriwaldi Syafriwaldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main issue addressed in this thesis is how the Sulit Air Sepakat (SAS) Organization contributes to Nagari Sulit Air in Solok Regency. The objective of this discussion is to understand the contributions of the SAS Organization to Nagari Sulit Air and to identify the supporting and inhibiting factors for the SAS Organization in assisting Nagari Sulit Air. The research type employed is qualitative research, which is descriptive in nature, aimed at obtaining data related to the researched issue. Data collection techniques utilized include interviews, observations, document analysis, and qualitative data analysis. Based on the research findings, it is revealed that the contribution of the Sulit Air Sepakat (SAS) Organization to Nagari Sulit Air plays a vital role in the development of the community, encompassing fields such as education, infrastructure, and religious matters. Initiatives like providing scholarships to local children within and outside Nagari Sulit Air, constructing places of worship, road development, and more, have significantly impacted the community. However, these efforts have faced challenges due to the contagious COVID-19 pandemic, which has hindered the local economy in recent years, affecting SAS's funding and causing disruptions in educational initiatives. Furthermore, the tourism sector in Sulit Air has not progressed due to inadequate management. The journey of the SAS Organization has encountered hurdles such as insufficient funding and difficulties in coordinating member schedules, which has impeded its smooth operation.